Media jako źródło zaspokajania fundamentalnych potrzeb. Rozważania w kontekście teorii „użytkowania i gratyfikacji” - Turska-Kawa, Agnieszka (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The role of media in fulfilling the basic needs. Considerations in the context of the “uses and gratifications” theory The impact of media on both individuals and societies has always attracted much attention in the work of scholars engaged in communicational sciences. The paper is a reflection on the relationship between media and the needs of individuals. The author presents a number of studies that have contributed to the consolidation of the “uses and gratifications” theory and in the same time have designated the stages of its development. By examining the relationship between psychological classifications of needs (in particular Saymour Epstein’s Cognitive Self Theory – CEST) and the benefits of individual’s contact with media (in the classification of Denis McQuail), the author shows the role of media in the fulfilling the basic needs, indicating their high impact on the lives of individuals. Key words: uses and gratifications theory, media, communicational sciences, fulfilling the basic needs